Zróżnicowania rozwoju społeczno-gospodarczego w Polsce na początku XXI wieku - Pięta-Kanurska, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Contemporary space of Poland is characterized by differentiations of socio-economic development level. They are mainly results of following historical processes, which went the country. Moreover the disproportions are increasing. That is why in the article conducted the analyses of the level of them using chosen socio - economic indicators. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 36-43